Investigação de vírus causadores de infecções no sistema nervoso central, em pacientes pediátricos, atendidos em um hospital de referência de Belo Horizonte, Minas Gerais - Eni da Conceição Rocha (2024)
ABSTRACT This research comprises a study, based on a mixed-methods approach, aimed at describing the inclusion of graduates from the Professional Master's Program in Technological Innovation and Intellectual Property (MPITPI), offered at the Federal University of Minas Gerais (UFMG), into the innovation ecosystem of the state of Minas Gerais. The target audience selected for the study consisted of alumni from the ten MPITPI cohorts who began and completed the program between 2011 and 2020, totaling 102 graduates. Of these, 66 participants responded to the electronic survey, representing 65% of the target group. To complement the quantitative research, a focus group interview was conducted with seven course alumni. In conclusion, it was found that the MPITPI, which celebrates its 15th anniversary in 2024, has contributed to the innovation ecosystem in Minas Gerais by providing highly qualified human capital for productive sectors and generating goods and services that positively impact society. Additionally, the research proved to be relevant, as it produced significant data to support the continuous improvement of the program.